The Effectiveness of ARIMA Method in Rice Production Forecasting of North Sumatera Province (Talenta Publisher, 2022)
Rice production continues to be spurred to meet the increasing need for food. Meanwhile, based on data from the Badan Pusat Statistik, in 2019 there was a decline in national rice production, especially in North Sumatra Province. In this research, it was found that the estimated amount of rice production for the next 8 periods was obtained using the Box Jenkins ARIMA method with the ARIMA model (2,0,6) experiencing an up and down trend, The MAPE (Mean Absolute Percentage Error) deviation value is obtained by 12.84%, the forecast model is quite efective to be used.